The Effect of School Governance on the Prevalence of KCSE Examination Cheating in Public and Private Secondary Schools in Kisii County, Kenya - Shibo, Margaret Nekesa; Fredrick O. Ogola, Fredrick O.; Gori, Justus (Scholars Middle East Publishers, 2017)
The purpose of this paper is to highlight on the effect of school governance on the prevalence of KCSE examination cheating in public and private secondary schools in Kisii County of Kenya. The study employed ex post facto and survey research design. The target population comprised of 1119 subjects comprising of principals, invigilators and examination officers drawn from 317 public and 46 private secondary schools in Kisii County. A sample of 109 principals, 218 invigilators and 10 examination officials was selected through stratified random sampling so as to participate in the study. The study utilized questionnaires to collect data. The instruments were tested for reliability and adapted after they scored 0.752 and 0.765 for the Invigilators’ questionnaire and School Principals’ questionnaire respectively. The study collected both qualitative and quantitative data. Pearson Correlation Coefficient was used with the help of SPSS to analyze quantitative data. Qualitative data was analyzed by use of descriptive analysis, by categorizing results into tables. The findings show that the current efforts put in place by KNEC to ensure compliance with the set rules and regulations to stop examination cheating in public and private secondary schools in Kisii County are not adequate. Following the findings, the study recommends that KNEC considers mobilizing resources to upscale its measures to check on examination cheating and resources to support use of modern technology to monitor KNEC examinations in Kisii County.
Keywords: School governance; KCSE examination; Prevalence.